PENGARUH VARIASI WAKTU FERMENTASI TERHADAP KADAR LAKTOSA, LEMAK, pH DAN KEASAMAN PADA SUSU SAPI YANG DIFERMENTASI MENJADI YOGURT - Yeni Agustina; Rudi Kartika; Aman S Panggabean (JURNAL KIMIA MULAWARMAN, 2015)
Yogurt is a fermentation milk product with bacteria Streptococcus thermophillus and Lactobacillus bulgariccus which has been commonly used in the process of making yogurt. The purpose of this study was to determine the effect of fermentation on the levels of lactose, fat, pH, acidity in yogurt. Determination of lactose in volumetric according Gohr, fat content carried by the Gerber method, using a pH meter pH and acidity values using titration.Keywords : lactose, fat, pH, acidity, fermentation, yogurt.